Fast-Tracking Full Citizenship in the Context of the Swiss Integration Stage Model - Kurt, Stefanie (My University, 2017)
In 2014, the Federal Assembly adopted the new Swiss Citizenship Act, which will enter into force on the 1st of January 2018. One of the missions of this Act is to align the pre-conditions for Swiss Citizenship with the Swiss integration stage model, a controversial move by the Federal Assembly that tightens the rules for access to citizenship and consequently narrows the space of cantonal policy. Under the new rule, only permanent residents (C-permit holders) would be entitled to Swiss citizenship. Consequently, the examination of the integration achievements of all foreigners who wish to naturalize in Switzerland has been intensified in an “ex ante” optic, due to the prerequisite of the C-permit. As the requirement of the early grant of the C-permit falls within the jurisdiction of the 26 cantons, the new rule will hardly obtain the desired result of harmonizing the path to Swiss citizenship. With reference to the two keywords of Swiss integration policy, requiring and promoting, which state the requirements and individual responsibilities of a foreign person with regard to integration and the promotion of equal opportunities, this article gives a first impression of the cantonal requirements for obtaining the C-permit in the case of successful integration. Further, it gives an overview of integration promotion factors, such as the right to a long-term stay, political rights, and the right to family reunification, all of which are connected to the legal status of the Cpermit and can determine the extent to which the path to citizenship remains open. It critically assesses the division of competence - national/cantonal - in the framework of integration policy and citizenship rights, concluding that the attempted “uploading” of the issue has resulted in strengthening rather than weakening the cantonal layer of citizenship governance.
Keywords: Switzerland; Citizenship; Cantonal legal diversity; Integration; Permanent residence permit